The Degradation of Airway Epithelial Tight Junctions in Asthma Under High Airway Pressure Is Probably Mediated by Piezo-1 - Zhou, Jia; Zhou, Xiang-dong; Xu, Rui; Du, Xian-zhi; Li, Qi; Li, Bin; Zhang, Guo-yue; Chen, Ling-xiu; Perelman, Juliy M.; Kolosov, Victor P. (Frontiers in Physiology, 2021)
Full functioning of the airway physical barrier depends on cellular integrity, which is coordinated by a series of tight junction (TJ) proteins. Due to airway spasm, edema, and mucus obstruction, positive end-expiratory alveolar pressure (also termed auto-PEEP) is a common pathophysiological phenomenon, especially in acute asthma attack. However, the influence of auto-PEEP on small airway epithelial TJs is currently unclear. We performed studies to investigate the effect of extra pressure on small airway epithelial TJs and its mechanism. The results first confirmed that a novel mechanosensitive receptor, piezo-1, was highly expressed in the airway epithelium of asthmatic mice. Extra pressure induced the degradation of occludin, ZO-1 and claudin-18 in primary human small airway epithelial cells (HSAECs), resulting in a decrease in transepithelial electrical resistance (TER) and an increase in cell layer permeability. Through in vitro investigations, we observed that exogenous pressure stimulation could elevate the intracellular calcium concentration ([Ca2+]i) in HSAECs. Downregulation of piezo-1 with siRNA and pretreatment with BAPTA-AM or ALLN reduced the degradation of TJs and attenuated the impairment of TJ function induced by exogenous pressure. These findings indicate the critical role of piezo-1/[Ca2+]i/calpain signaling in the regulation of small airway TJs under extra pressure stimulation.